Correlation between human papillomavirus viral load and cervical lesions classification: A review of current research - Yilu Zhou; Xiaoyu Shi; Jiaxin Liu; Lina Zhang (Frontiers in Medicine, 2023)
Cervical cancer is the fourth largest malignant tumor among women in the world. Human papillomavirus (HPV) infection can lead to cervical intraepithelial neoplasia (CIN) and cervical cancer. Active papillomavirus infection occurs when the infected basal cells replicate and fill a certain area. Persistent HPV infection can lead to squamous intraepithelial lesions, which are divided into CIN1, CIN2, and CIN3 according to how much epithelium is impacted. Different types of HPV have different possibilities of causing cervical cancer, and high-risk HPV is the main cause of cervical cancer. Research showed that viral load may be an indicator of the progression of cervical precancerous lesions, but this association does not seem to be universal. This article aims to summarize different genotypes, multiple infections, especially viral load, in cervical precancerous lesions, to guide early intervention.